Some Principles for Development of Statistics for a Gulf Cooperation Council Currency Union - Krueger, Russell (IMF Working Papers; Working Paper ;, 2006)
Looking ahead to the creation of a Gulf Cooperation Council (GCC) Currency Union in 2010, the paper covers some implications for the statistical programs of the GCC countries. Despite uncertainty over the structure of the proposed union, the paper envisions several types of mutually reinforcing statistics-convergence criteria, statistics on the core policy variables and instruments, additional macroeconomic data, specialized statistics related to the economic and institutional conditions within the union, and public information. Major changes to national statistical programs are needed that should begin soon.